2013
DOI: 10.1063/1.4791675
|View full text |Cite
|
Sign up to set email alerts
|

More than one order enhancement in peak detectivity (D*) for quantum dot infrared photodetectors implanted with low energy light ions (H−)

Abstract: In(Ga)As/GaAs-based quantum dot infrared photodetectors (QDIPs) have emerged as one of the most suitable devices for infrared detection. However, quantum dot devices suffer from lower efficiencies due to a low fill-factor (∼20%–25%) of dots. Here, we report a post-growth technique for improving the QDIP performance using low energy light ion (H−) implantation. At high bias, there is evidence of suppression in the field-assisted tunneling component of the dark current. Enhancement in peak detectivity (D*), a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our study showed that a quaternary InAlGaAs capping always achieved better dot quality; therefore, we used it as the capping layer of the InGaAs/GaAs QDIP structure for the electrical study (Fig. 2) [26]. The QDIP heterostructure was implanted with a stable beam of 3 MeV protons at a fluence of 2.0 Â 10 12 ions/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study showed that a quaternary InAlGaAs capping always achieved better dot quality; therefore, we used it as the capping layer of the InGaAs/GaAs QDIP structure for the electrical study (Fig. 2) [26]. The QDIP heterostructure was implanted with a stable beam of 3 MeV protons at a fluence of 2.0 Â 10 12 ions/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…10). We believe that the dot size within the QDIP increased because of proton implantation [26]. TRIM calculations [27] show that during implantation, ions are subjected to electronic and nuclear energy losses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, InAs/GaAs QDIPs have been extensively investigated due to their advantageous properties, such as sensitivity to normal incident infrared radiation and weak thermionic coupling between the ground state and excited states, compared to quantum well IPs (QWIPs), resulting in reduced dark current. In the past few years, the intersubband photoresponse of n-type QD detector structures have been the subject of intense research [3][4][5][6]. However, high-temperature operation of n-type QDIPs has still remained a challenging problem although the hydrogenbased treatment processes were conducted to suppress the dark current [5,6].…”
mentioning
confidence: 99%